Dokazi o učinkovitosti uporabe robota in navidezne resničnosti v rehabilitaciji - Matjačić, Zlatko (Rehabilitacija (Ljubljana), 2011)
Background: Rehabilitation robotics and virtual environments are being gradually used in clinical rehabilitation environments as they enable higher number of specific movement (mobility or upper limb) repetitions while at the same time relieving physiotherapists from strenuous labor. However, as rehabilitation robotics require relatively high initial investment evidences on its efficacy are crucial for their further wide-spreading. Methods: We reviewed literature reporting on randomized clinical trials (RCT) that compared efficacy of rehabilitation robots and virtual environments with conventional therapeutic approaches in the field of mobility and upper limb rehabilitation. Results: According to the criteria on the level of evidences adopted by Evidence-Based Review on Stroke Rehabilitation (www.ebrsr.com), we established that there are strong (Level 1a) evidences that: i.) Rehabilitation robots for mobility training are as effective as conventional treatment, ii). Training with robotic devices improves upper extremity functional outcomes and motor outcomes of shoulder and elbow, while do not improve motor outcome of wrist and hand, iii). Virtual reality treatment can improve motor function in the chronic stage of stroke. Conclusions: Rehabilitation robotics and virtual environment technologies have significant potential for the processes of physical medicine and rehabilitation.
Keywords: efficiency; Evidence-Based Medicine; haptična robotika; navidezna resničnost; Nondirective Therapy; Occupational Therapy; rehabilitacija; Robotics; učinkovitost; vocational rehabilitation